CAMPUR KODE DALAM NOVEL BIDADARI BERMATA BENING KARYA HABIBURAHMAN EL SHIRAZY - Safitri, Nur Erma; Saman, Sisilya; Abdussamad, Abdussamad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is motivated by communication strategy of bilingualisme person that affect to his literary work. The problem that discussed in this research is existence, background, and causatue factor of mix code in the novel Bidadari Bermata Bening by Habiburahman El Shirazy. The purpose of this research is to describe based on the research problem. This research use a description method with qualitative form. The data sourse in this research is the novel Bidadari Bermata Bening by Habiburahman El Shirazy. The data in this serearch is word that contain data source in the form insert the word, phrases, clauses, repeat word, baster, and idiom. Technique of this serearch is sereach technique using documentary. Data collection tool of this serearch is stationary and laptop that use to record the data. Based on data analysis there is 74 data in Bidadari Bermata Bening by Habiburahman El Shirazy that analyzed. Mix code of phrases is 16 data that including 8 data of Java languange and 8 data of Arabic languange. Mix code of repeat word is 9 data of Java languange. The causative factor of mix code is 39 data of limitations of user code,7 data of users popular terms and 28 data of partners talk. Keywords: Novel Bidadari Bermata Bening, Mix Code, Sociolinguistics